Students with LD at Postsecondary: Supporting Success and the Role of Student Characteristics and Integration. Issue 1 (15th December 2019) - Goegan, Lauren D.; Daniels, Lia M.
Abstract: Students with learning disabilities (LD) are attending postsecondary education more than ever, but are also less likely to complete their education compared to non‐LD peers. Using the Inputs–Environment–Outcomes model of Astin, we examined students with LD and non‐LD peers during their first year of postsecondary studies. Using structural equation modeling, we found that for all students, perceived academic ability had a positive direct effect on outcomes, whereas drive to achieve had only an indirect effect. Academic integration was important for grade point average and satisfaction. Social integration was important for the acquisition of knowledge and skills and satisfaction, and these connections were stronger for students with LD. Our discussion highlights potential supports for students with LD.